Tuberculous Lymphadenitis in Immunocompromised Patients: Case Series - Edward Pandu Wiriansya; Irawaty Djaharuddin; Andi Tiara Salengke Adam (Jurnal Respirasi, 2022)
Introduction: Tuberculous lymphadenitis (TBLN) is a form of extra-pulmonary TB with clinical features ranging from lumps to abscesses. Human Immunodeficiency Virus (HIV) co-infection and diabetes mellitus alongside TBLN made the diagnosis and management exceptionally challenging. We reported 3 cases of TBLN, 2 among them had an existing HIV co-infection, and 1 had preexisting diabetes mellitus.Case: The first case, a 28-year-old man, previously diagnosed with HIV, complained of a lump in the neck; biopsy results suggested TBLN. The second case was a 36-year-old man with a neck abscess and HIV co-infection. Acid Fast Bacilli (AFB) pus was positive & Human Immunodeficiency Virus Enzyme-Linked Immunosorbent Assay (HIV ELISA) was reactive. The third case was a patient with a neck abscess with preexisting diabetes mellitus (DM) underwent wound debridement and was given anti-tuberculosis drugs.Conclusion: TBLN with HIV co-infection or diabetes had clinical features ranging from a painful lump to an abscess. The definitive diagnosis was taken by examining AFB from pus. If the abscess was more extensive than or equal to 3 cm, wound debridement was necessary. The primary treatment for TBLN was anti-tuberculosis drugs and required even greater attention if a patient had any preexisting comorbidities such as HIV and diabetes.